Cretaceous beds in the eastern extensions of the Karavanke Alps and the Sava folds - Šribar, Ljudmila (Geologija, 1981)
Erosional remmants of Cretaceous beds in the eastern extensions of the Karavanke Alps and of the Sava folds in Slovenia are discussed from the biostratigraphic point of view. Their lower part appears to have been accumulated continuously in deep sea as indicated by microfossils. Three biozones can be distinguished. The first is evidenced by calpionelids and is transitional in character; its stratigraphic range is Upper Tithonian to Valanginian. The second comprises Hauterivian to Aptian layers and is characterized by radiolarians in general. At some distance from former land the upper part of this biozone passes out and in the same series prevail terrigenous sediments. Here occur abundant redeposited Jurassic and Cretaceous microfossils. The third biozone includes Albian-Cenomanian deposits and is identified by Hedbergella trocoidea and Rotalipora ticinensis. The Turonian stage can not be recognized, the Senonian stage is, however, well defined by globotruncanas.